Association between CYP2A13 polymorphisms and lung cancer: A protocol for systematic review and meta-analysis. Issue 50 (11th December 2020) - Ma, Long; Jin, Gang; Yang, Yi; Pang, Yao; Wang, Wenhao; Zhang, Hongyi; Liu, Jiawei; Wu, Peng; Wang, Zequan; Wang, Kui; Chang, Ruitong; Li, Jialong; et al.
Abstract: Background: Recently, lung cancer has become the most common cause of cancer-related death, several studies indicate that the cytochrome P450 2A13 (CYP2A13) polymorphisms may be correlated with lung cancer susceptibility, but the results have been inconsistent and inconclusive. Therefore, the aim of this meta-analysis is to provide a precise conclusion on the potential association between CYP2A13 polymorphisms and the risk of lung cancer based on case-control studies. Methods: The PubMed, Embase, Cochrane Library, Web of Science, and China National Knowledge Infrastructure (CNKI) databases will be searched for case-control studies published up to September 2020. Odds ratio (OR) and 95% confidence interval (95% CI) were used to determine the effects of the CYP2A13 polymorphism on lung cancer risk, respectively. Results: The results of this meta-analysis will be submitted to a peer-reviewed journal for publication. Conclusion: This meta-analysis will summarize the association between CYP2A13 polymorphisms and the risk of lung cancer. INPLASY registration number: INPLASY202090102